Resolving Puzzles of Monetary Policy Transmission in Emerging Markets - Jongrim Ha; Dohan Kim; M. Ayhan Kose; Eswar Prasad (Institute of Labor Economics (IZA), 2024)
Conventional empirical models of monetary policy transmission in emerging market economies produce puzzling results: monetary tightening often leads to an increase in prices (the price puzzle) and depreciation of the currency (the FX puzzle). We show that incorporating forward-looking expectations into standard open economy structural VAR models resolves these puzzles. Specifically, we augment the models with novel survey-based measures of expectations based on consumer, business, and professional forecasts. We find that the rise in prices following monetary tightening is related to currency depreciation, so eliminating the FX puzzle helps solve the price puzzle.
Keywords: E31; E32; Q43; 330; monetary policy; emerging market economies; prize puzzle; foreign exchange puzzle